Polycyclic aromatic hydrocarbons in fish from remote and high mountain lakes in Europe and Greenland - Vives, Ingrid; Grimalt, Joan O.; Fernández Ramón, M. Pilar; Rosseland, B. O. (Science of The Total Environment, 2004)
11 pages, 4 figures, 3 tables.-- PMID: 15081697 [PubMed].-- Available on line Dec 16, 2003. Polycyclic aromatic hydrocarbons (PAHs) were analysed in liver of fifty-seven individual trout distributed among seven high mountain lakes in Europe and one remote lake in Greenland. In all cases, very similar distributions were observed in which phenanthrene largely predominated and fluoranthene and pyrene were the second major compounds. These distributions were similar to those observed in the dissolved fraction of the waters studied in three of these lakes. The range of concentrations of PAH in fish liver show only a five-fold variation, which is considerably smaller than the range more than two orders of magnitude of sedimentary PAH concentrations of these lakes. No correlation between PAH content in sediments and fish liver has been found both at the level of total and individual compounds. However, lake site is the main statistically significant factor of variability between PAH concentrations in fish liver. Changes in fish species explain significant differences in liver content of some PAHs. Within lake, condition factor and liver concentration are inversely correlated. Female fish display lower average concentrations than male in all lakes but the differences are not statistically significant. No correspondence between fish age and PAH content has been observed. Financial support from the EU project EMERGE (EVK1-CT-1999-00032) is acknowledged. Peer reviewed